Mutualism Disruption Threatens Global Plant Biodiversity: A Systematic Review. - Clare E Aslan; Erika S Zavaleta; Bernie Tershy; Donald Croll (PLoS ONE)
Background As global environmental change accelerates, biodiversity losses can disrupt interspecific interactions. Extinctions of mutualist partners can create "widow" species, which may face reduced ecological fitness. Hypothetically, such mutualism disruptions could have cascading effects on biodiversity by causing additional species coextinctions. However, the scope of this problem - the magnitude of biodiversity that may lose mutualist partners and the consequences of these losses - remains unknown. Methodology/principal findings We conducted a systematic review and synthesis of data from a broad range of sources to estimate the threat posed by vertebrate extinctions to the global biodiversity of vertebrate-dispersed and -pollinated plants. Though enormous research gaps persist, our analysis identified Africa, Asia, the Caribbean, and global oceanic islands as geographic regions at particular risk of disruption of these mutualisms; within these regions, percentages of plant species likely affected range from 2.1-4.5%. Widowed plants are likely to experience reproductive declines of 40-58%, potentially threatening their persistence in the context of other global change stresses. Conclusions Our systematic approach demonstrates that thousands of species may be impacted by disruption in one class of mutualisms, but extinctions will likely disrupt other mutualisms, as well. Although uncertainty is high, there is evidence that mutualism disruption directly threatens significant biodiversity in some geographic regions. Conservation measures with explicit focus on mutualistic functions could be necessary to bolster populations of widowed species and maintain ecosystem functions.